Resilience and Resistance: A Feminist Perspective of Women and the National Liberation Struggle for the Independence of Western Sahara - Ilesanmi, Omotola Adeyoju (Universitas Medan Area, 2025)
This paper examines the role of Saharawi women in the national liberation struggle for Western Sahara's independence through the lens of Feminist National Liberation Theory. It examines their contributions to political activism, administration, governance, and transnational advocacy, as well as the oppression women faced under Moroccan colonialism and the Saharawi liberation struggle. Sahrawi women suffer torture, arbitrary detention, and sexual harassment as a result of their resistance to the Moroccan occupation and struggle for self-determination. This paper adopts the Feminist National Liberation Theory to examine how Saharawi women have been both active agents and symbolic pillars of resilience and resistance in their efforts to challenge colonial oppression. It employs a qualitative historical analysis and feminist critique of women's roles in the independence struggle, using secondary sources of data, including historical documents, reports, and academic literature. t. The paper argues that women’s agency is not secondary but fundamental to independence struggles and that national independence cannot be achieved without gender justice, positioning Saharawi women as both symbols and agents of resilience and resistance.